2018
DOI: 10.1016/j.aca.2018.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric ionophore-based coextraction titrimetry of potassium ions

Abstract: Potassium ion concentration can be successfully determined volumetrically by moving the titration from a homogeneous phase to a two phase solvent system. This is because potassium can be readily complexed in a selective and thermodynamically stable manner by ionophores such as valinomycin. Previous work demonstrated the successful titration of potassium by ion-exchange into an organic phase containing valinomycin, but the sample itself served as titrant, which is not sufficiently practical for routine applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Optical sensors are generally characterised by a slightly simpler operation over ion-selective electrochemical sensors which require careful calibration, temperature and pH control. 7 Typically, solution phase optical sensors for Na + and K + and other metal ions have been based on size-selective heteroatomcontaining macrocycles such as the crown ether, 8,9 azacrown, 10,11 cryptand 12 or calixarene 13,14 as the binding unit. The binding unit is covalently bonded to a chromophore or fluorophore which exhibits a change in absorbance or fluorescence properties as a result of the binding event.…”
Section: Introductionmentioning
confidence: 99%
“…Optical sensors are generally characterised by a slightly simpler operation over ion-selective electrochemical sensors which require careful calibration, temperature and pH control. 7 Typically, solution phase optical sensors for Na + and K + and other metal ions have been based on size-selective heteroatomcontaining macrocycles such as the crown ether, 8,9 azacrown, 10,11 cryptand 12 or calixarene 13,14 as the binding unit. The binding unit is covalently bonded to a chromophore or fluorophore which exhibits a change in absorbance or fluorescence properties as a result of the binding event.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, some studies on micro-batchwise titration have been reported. 4,5 This study aims to develop an alternative and cost-effective approach to make the reagent reusable in conventional batch titration towards a green chemical analysis. Moreover, natural reagents were also of interest as alternatives to commercial synthesized chemicals.…”
Section: Introductionmentioning
confidence: 99%